Entrepreneurship and industry in India, 1800-1947 - Ray, Rajat Kanta (Delhi : Oxford University Press, 1994)
Contributed articles.
Includes bibliographical references.
Keywords: Industries -- India -- History; Entrepreneurship -- India -- History